2008
DOI: 10.1007/s00415-008-0962-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological features of late-onset transthyretin Met30 familial amyloid polyneuropathy unrelated to endemic foci

Abstract: Electrophysiological differences between late- and early-onset cases were present, probably reflecting the different underlying pathogenic mechanisms of neuropathy. The demyelinating feature does not exclude the possibility of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 41 publications
3
64
0
1
Order By: Relevance
“…Detailed descriptions of the severity of these deficits are only available in individual case reports. Despite large studies of the main clinical features of LateMet30 FAP,11, 35 no controlled studies have focused on the clinical features of FAP neuropathies in Val107 and Tyr77 carriers. Almost all our patients exhibited autonomic dysfunction, as previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed descriptions of the severity of these deficits are only available in individual case reports. Despite large studies of the main clinical features of LateMet30 FAP,11, 35 no controlled studies have focused on the clinical features of FAP neuropathies in Val107 and Tyr77 carriers. Almost all our patients exhibited autonomic dysfunction, as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Early onset Met30 autopsy studies showed more severe amyloid deposition in sympathetic than dorsal root ganglia, with the opposite pattern in LateMet30. Another study35 compared sural nerves biopsies from early onset to late onset Met30 patients and found predominantly small‐fiber loss for the first. Scarce amyloid deposition casts doubt on the pathogenicity of these deposits.…”
Section: Discussionmentioning
confidence: 99%
“…The demyelinating feature suggested by NCS has been reported as the most common pitfall in diagnosing sporadic cases of FAP (10), and in some late-onset FAP patients with ATTR V30M, the slowing of conduction velocity and prolongation of distal latency were reported to be conspicuous (11). In fact, the electrophysiological findings of the right ulnar nerve observed in our patient also hampered the correct diagnosis in our patient.…”
Section: Discussionmentioning
confidence: 56%
“…In FAP with ATTRVal30Met it has been shown that the clinical picture and the histopathological and electrophysiological findings of peripheral nerve lesions are considerably different between patients with early-onset type and those with late-onset type [10,[15][16][17]: the latter group of patients frequently has serious cardiac involvement [37], and upper limb neuropathy may develop at an earlier stage of the disease than previously recognized [38,39]. Histopathology of dorsal root ganglia shows a more selective loss of small neurons in early-onset patients [40], while loss of neurons of all sizes is seen in late-onset patients [15].…”
Section: Difference In Pathophysiology Between Endemic-versus Non-endmentioning
confidence: 99%
“…An anticipation phenomenon is also observed only in endemic patients [11][12][13][14]. It was recently shown that histopathological and electrophysiological Kodaira et al 4 of 26 findings of peripheral nerve lesions differed between the two groups [15][16][17]. Although genetic, gender and environmental factors, and aging are surmised to be the causes of these differences, the details remain unclear.…”
Section: Introductionmentioning
confidence: 99%